ANALISIS TREND JUMLAH PENUMPANG KAITANNYA HARGA TIKET PADA KERETA API LOGAWA TAHUN 2011-2013 DAOP IX JEMBER - Fitria Wahyu Anggraini; Retna Ngesti S (Economic Education, University of Jember, 2015)
This study aims to determine the trend of the number of train passengers Logawa years 2011-2013 relating to ticket prices in Daop IX Jember. Determining the location of the study using purposive area. The main data is secondary data, data collection techniques using documents, observation, and interviews. Analysis of the data using trend analysis with Least Square method. The results showed that the trend of the number of train passengers Logawa years 2011-2013 decreased. Logawa rail passenger numbers decrease with the price change. When prices rise, the number of passengers has decreased. People prefer other transportation as a substitute bus train Logawa such as, travel, or personal vehicles more affordable. The number of train passengers Logawa also influenced by other factors, such as community needs to use the train Logawa. The decrease trend of the number of passengers in 2011-2013 led to predictions of the number of train passengers Logawa 2014 also decreased.